FROM ACTION LEARNING TOTHETEACHING ORGANIZATION: An Experiential Approach - Pawitra, Teddy; Chan, K. C. (Gadjah Mada International Journal of Business, 2003)
This paper expounds action learning for effective change leadership development using the learning-teaching helix as a paradigm for individualâs introspection. Which consists of five phasesâAwareness phase (as certain your strengths and weaknesses). Alignment phase (identify your core competence). Action phase (synthesize your work, business and management skills), Adoption phase (becoming a leader) and Assurance phase (excel as an educator cum coach). In addition, to succeed, the individual has to plan, strategize, prioritize and integrate. As a holistic manager the individual needs to think, feel and do to evolve from continuous action learning to the cycle of teaching for continuous innovation in organizational performance capabilities.